A description of the advertising and direct marketing decision processes of the New Zealand marketing managers - Thirkell, Peter; Stewart, David (School of Management Working Papers, 1992)
A critical component of the marketing mix for most organisations is the development and execution of an effective communications strategy. Yet managers often have little guidance in advertising and promotional decisions other than past practice within their own organisations, or rules of thumb formed over years of training and experience. The New Zealand Advertising and Direct Marketing Project was initiated as a baseline study with the objective of better understanding the beliefs, opinions and practices of marketing managers in respect of marketing communications within their orgainsations. A sample of about 200 large companies known to have reasonably significant advertising budgets was surveyed late in 1991. A usable sample of 91 actual responses forms the basis of a generally descriptive survey which examines: what managers believe about advertising and its effects, how the advertising function is organised, the setting and allocating of budgets, rules of thumb which guide advertising practice, measures of advertising effectiveness, and general issues to do with the future of advertising and direct marketing. The results provide an interesting benchmark against which practitioners can assess their own particular beliefs and practices, as well as a good overview of management practice for marketing students and educators. Where appropriate, the results are broken down into four predominant industry categories: fastmoving consumer goods, consumer durables, financial services, and business to business marketers.